(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article deals with linguistic contrastive and linguistic methodological aspects of anthropocentric proverbs of English, Russian, Uzbek, and Kazakh languages. Anthropocentric proverbs in all languages express the concept of man in two ways: explicitly and implicitly. The analysis and comparison of anthropocentric proverbs of diverse languages make it possible to identify in them the universal and national-cultural characteristics of both society as a whole and man in particular. Linguistic theoretical and comparative analysis and description of proverbs provides material for its linguistic didactic description and the possibility of their implementation in the educational process.